Physiological pacing to improve cardiac resynchronization therapy non-responder and a tryst with calcified septum—a case report - Vanita Arora (The Egyptian Heart Journal, 2021)
Abstract Background As per the literature, patients with intraventricular conduction delay (IVCD) do not respond well to cardiac resynchronization therapy (CRT) alone. They need advanced technological approach and out of the box thinking for a good response. Case Ours is a case of ischemic cardiomyopathy with wide QRS-IVCD, a non-responder to CRT. While planning for replacement of the device for early replacement indicator (ERI), we decided to do His-optimized CRT/left bundle optimized CRT (HOT-CRT/LOT-CRT) for the patient. Conclusion The challenges we faced with the present available hardware paved a way for insisting on the limitation of the available lumenless lead to penetrate calcified the septum and importance of the pre-procedure evaluation of intraventricular septum (IVS) for calcification by more than just echocardiography.